Eduplay and Fun dalam Interior Pusat Edukasi Seni untuk Anak di Surabaya - Samantha Mulia; Laksmi Kusuma Wardani; Celline Junica (Intra, 2017)
Children have high curiosity and creativity. Their curiosity and creativity can be directed in a positive way so that they can find their talent and interest earlier. Creativity can be channeled through art. The design provides education art center for children to try new things and improve their creativity at an early age. The design contains class facilities such as painting, clay, art paper, cake decoration, flower arrangement, batik, multipurpose class, and another facilities such as library, cafe, office, lobby and playing area. The concept of